2013
DOI: 10.1080/09670262.2013.786791
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of the widespreadMartensia fragiliscomplex (Delesseriaceae, Rhodophyta) from the Indo-Pacific region reveals three new species ofMartensiafrom Taiwan

Abstract: The genus Martensia is characterized primarily by its unique thallus morphology, wherein a proximal membranous blade is interrupted distally by one to several bands of net-like tissue (networks). Among the known species, M. fragilis is characterized by fan-shaped, membranous blades with multiple bands of networks. The species has been frequently reported from warm temperate and tropical regions. Collections from various localities in the Indo-Pacific region included many specimens fitting this broad concept of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…53, Figures 1-4) with our Martensia specimens and discovered that Okamura's four morph types of Martensia resemble Lee's species concepts (2006Lee's species concepts ( , 2008 of M. australis (Figures 3 and 12), M. jejuensis (Figures 9 and 16), M. bibarii (Figures 4 and 13), and M. fragilis (Figures 7 and 15 Lin et al (2013: 187) that M. denticulata from Japan should be recognized as M. jejuensis. Lin et al (2013) mentioned that the changed environmental conditions, especially the enriched seawater from seashell farms, might have considerable effects on the growth and thallus morphology of Martensia populations around Jeju Island. It is noticeable that individuals having fragmented networks and linear membranous segments, such as M. jejuensis type and M. bibarii type, were collected mostly from somewhat sheltered and shallow places of Jeju Island.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…53, Figures 1-4) with our Martensia specimens and discovered that Okamura's four morph types of Martensia resemble Lee's species concepts (2006Lee's species concepts ( , 2008 of M. australis (Figures 3 and 12), M. jejuensis (Figures 9 and 16), M. bibarii (Figures 4 and 13), and M. fragilis (Figures 7 and 15 Lin et al (2013: 187) that M. denticulata from Japan should be recognized as M. jejuensis. Lin et al (2013) mentioned that the changed environmental conditions, especially the enriched seawater from seashell farms, might have considerable effects on the growth and thallus morphology of Martensia populations around Jeju Island. It is noticeable that individuals having fragmented networks and linear membranous segments, such as M. jejuensis type and M. bibarii type, were collected mostly from somewhat sheltered and shallow places of Jeju Island.…”
Section: Discussionmentioning
confidence: 98%
“…Mature tetrasporangia are borne on both sides of fertile blades, globose, 70-100 μm in diameter, and tetrahedrally divided ( Figure 59). Lin et al (2013) recently showed that the widespread Martensia fragilis in the northwestern Pacific Ocean (e.g., Taiwan, Korea, and Japan) contained several cryptic species, which share some morphological similarity. They also concluded that some morphological features used for separating species (e.g., size of network structure, blade shape, branching pattern) are not reliable, and they merged Martensia bibarii from Korea into Martensia jejuensis based on molecular and morphological evidence.…”
Section: Reproductive Structuresmentioning
confidence: 99%
See 3 more Smart Citations